2004
DOI: 10.1111/j.1600-0404.2004.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and affective status in mild hypothyroidism and interactions with l-thyroxine treatment

Abstract: From the analysis of the results, treatment of asymptomatic MH would seem advisable in order to re-set hormonal levels and, particularly in older subjects, to protect the brain against the potential risk of cognitive and affective dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 40 publications
2
63
0
5
Order By: Relevance
“…Cloyra Almeida, 1 Marco Antônio Brasil, 2 Antônio José Leal Costa, 3,4 Fabiola A A Reis, 5 Vaneska Reuters, 6 Patrícia Teixeira, 6 Márcia Ferreira, 6 Amanda M Marques, 7 Bianca A Melo, …”
unclassified
“…Cloyra Almeida, 1 Marco Antônio Brasil, 2 Antônio José Leal Costa, 3,4 Fabiola A A Reis, 5 Vaneska Reuters, 6 Patrícia Teixeira, 6 Márcia Ferreira, 6 Amanda M Marques, 7 Bianca A Melo, …”
unclassified
“…Studies about the neuropsychological and behavioral characteristics of patients with SH reported significant deficiencies in the abilities related to memory (12) and logical memory (13). A reduction was observed in the total memory coefficient, but it was not significant (13).…”
Section: Discussionmentioning
confidence: 93%
“…Baldini et al (1997) and Bono et al (2004) found an association between the SH and neuropsychological alterations, as for the logical memory, attention, global cognitive functioning and some executive functions. The memory deficit reported by Bono et al (2004) was related only to age.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Diversos trabalhos têm mostrado melhora do desempenho cognitivo com o tratamento, porém sem consenso definido na literatura (10,11,14,17,18). Contudo, caso seja evidenciada a potencialidade do tratamento nesses casos, a subsequente melhora da qualidade de vida deve ser analisada para se avaliar uma indicação formal do uso da levotiroxina em pacientes com HS.…”
Section: Discussionunclassified